PENGURANGAN KERUSAKAN LINGKUNGAN MELALUI PELAPORAN AKUNTANSI BIAYA RESTORASI PSAK 57 - Kesya Agnes Maria; Lodovicus Lasdi (Fakultas Bisnis Universitas Kristen Duta Wacana, 2023)
ABSTRACT Excessive exploitation of natural resources is still an unresolved issue. Even though Indonesia is a member of United Nations, it has an obligation to push for realization of Sustainable Development Goals (SDGs). One of the points of SDG 12 is to create sustainable patterns of production and consumption so that there is no overexploitation of natural resources. This study aims to determine indicators that can be used in determining the probability of occurrence in order to classify restoration costs as provisions or contingent liabilities in PSAK 57 so that they can support achievement of SDG 12. This qualitative research uses the descriptive and literature study method to develop indicators. The result obtained is an indicator of possibility outcome (IPOu), which is able to close the gaps contained in PSAK 57. As a result, the on-balance sheet for restoration costs increases, which will increase leverage, so companies are more careful in consuming resources. Keywords: Sustainable development goals, PSAK 57, Restoration cost, Provision, Indicator of Possibility Outcome. ABSTRAK Eksploitasi sumber daya alam yang berlebihan masih menjadi isu yang belum terselesaikan. Padahal sebagai anggota PBB, Indonesia memiiki kewajiban untuk mendorong terwujudnya Sustainable Development Goals (SDGs). Salah satu poin dari SDG 12 adalah menciptakan pola produksi dan konsumsi yang berkelanjutan, sehingga tidak boleh ada overeksploitasi sumber daya alam. Penelitian ini bertujuan untuk mengetahui indikator yang dapat digunakan dalam menetapkan probabilitas munculan dalam rangka mengklasifikasikan biaya restorasisebagai provisi atau liabilitas kontinjensi di dalam PSAK 57, sehingga dapat mendukung pencapaian SDG 12. Penelitian kualitatif ini menggunakan metode studi deskriptif dan studi kepustakaan dalam pembuatan indikator. Hasil yang diperoleh adalah Indicator of Possibility Outcome (IPOu) yang mampu untuk menutup celah yang terdapat dalam PSAK 57. Hasilnya, terjadi on-balance sheet biaya restorasi meningkat yang akan meningkatkan leverage, sehingga perusahaan lebih berhati-hati dalam melakukan konsumsi sumber daya. Kata kunci: Sustainable development goals, PSAK 57, Biaya restorasi, Provisi, Indicator of Possibility Outcome.